2014
DOI: 10.3389/fgene.2014.00354
|View full text |Cite
|
Sign up to set email alerts
|

Stratified randomization controls better for batch effects in 450K methylation analysis: a cautionary tale

Abstract: Background: Batch effects in DNA methylation microarray experiments can lead to spurious results if not properly handled during the plating of samples.Methods: Two pilot studies examining the association of DNA methylation patterns across the genome with obesity in Samoan men were investigated for chip- and row-specific batch effects. For each study, the DNA of 46 obese men and 46 lean men were assayed using Illumina's Infinium HumanMethylation450 BeadChip. In the first study (Sample One), samples from obese a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
43
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 44 publications
(46 citation statements)
references
References 32 publications
3
43
0
Order By: Relevance
“…Methylation values ranged from zero (for a fully unmethylated CpG site) to one (for a fully methylated CpG site). As others have found that the differences between plates or chips are often the largest source of technical variation [12,13], all pairs of placenta and cord blood (from the same individual) were arrayed on the same chip with a randomized position (row and column).…”
Section: Dna Methylation Profilingmentioning
confidence: 99%
“…Methylation values ranged from zero (for a fully unmethylated CpG site) to one (for a fully methylated CpG site). As others have found that the differences between plates or chips are often the largest source of technical variation [12,13], all pairs of placenta and cord blood (from the same individual) were arrayed on the same chip with a randomized position (row and column).…”
Section: Dna Methylation Profilingmentioning
confidence: 99%
“…Blood samples were collected blinded to the outcome, as well were DNA extraction and DNAm measurements. Batch effects are omnipresent and numerous for the 450K platform [24], but our careful sample allocation scheme ensured that they were not associated with the outcome or the matching factors.…”
Section: Discussionmentioning
confidence: 99%
“…We also considered microarray batch effects by stratified randomization of samples across chips. This approach was implemented to protect against spurious findings and represents a more optimal approach than common computational corrections for batch effects such as ComBat (32). The standardized intervention and relatively brief time period between sampling are also important factors to consider in this study.…”
Section: Discussionmentioning
confidence: 99%